Environmental Studies of English School: Case Study of Forest Fires in Indonesia and Transboundary Haze in Southeast Asia - Yani, Yanyan Mochamad; Robertua, Verdinand (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
Despite of its advantages in social dimension, English School still has limited articles on environmental issues. Many global ecological crisis has been dealt with constructivism and green theory because the failure of English Scholars to adopt new norms such as climate responsibility, sustainable development and environmental justice. This article would like to highlight the synthesis of the normative tensions and the regional studies within the environmental studies of English School using the case study of Indonesia ratification to ASEAN Agreement on Transboundary Haze Pollution. Pluralism and solidarism will be the conceptual instruments in criticizing the blindness of environmental analysis in the English School communities and also constructing the environmental-friendly English School theory. There are two main conclusions in this article. Firstly, Indonesia ratification of ASEAN Agreement of Transboundary Haze Pollution, the emergence of domestic environmental legislation and the adoption of environmental responsibility marked the end of pluralist hegemony in environmental studies. Secondly, Indonesia ratification of AATHP is one of the foundations of regional environmental governance in Southeast Asia.